2021
DOI: 10.21203/rs.3.rs-659195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cost of Inappropriate Referral Pathways in Inpatient Care for Three Major Noncommunicable Diseases in Mongolia: A Registry-Based Analysis

Abstract: Background: Non-communicable diseases (NCDs) consistently pose a huge economic burden to health systems and countries in general. The aim of this study was to quantify inpatient costs associated with chronic obstructive pulmonary disease, stroke and ischemic heart disease stratified by type of referral pathway, and to investigate key factors that drive these costs. Methods: A registry-based data analysis was performed using national public hospital inpatient records from 2016 to 2018 for 117,600 unique patient… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…For example, early rehabilitation may be an effective strategy to reduce the length of stays while improving patient outcomes. Our results also showed that advanced age was associated with higher hospitalization costs, which is consistent with previous studies [23][24]. A potential interpretation could be that older patients are more likely to have comorbidity and require more complex medical care [25].…”
Section: Discussionsupporting
confidence: 92%
“…For example, early rehabilitation may be an effective strategy to reduce the length of stays while improving patient outcomes. Our results also showed that advanced age was associated with higher hospitalization costs, which is consistent with previous studies [23][24]. A potential interpretation could be that older patients are more likely to have comorbidity and require more complex medical care [25].…”
Section: Discussionsupporting
confidence: 92%